Does cultural identity catalyze behavior? A TAM-based study on museum cultural creative products consumption in China - Changping Hu; Pengxiang Niu; Xiaoyi Chen; Pengxiang Cheng; Xiaojun Jiang; Rongfa Li; Ruiying Kuang (PLoS ONE, 2026)
China’s cultural creative products are highly homogenized and can no longer meet the growing aesthetic needs of Chinese consumers. In the museum sector, the sluggish sales of cultural and creative products have become a pain point in its development. Research on consumers’ perceptions and purchase intentions regarding museum cultural creative products has grown significantly in recent years, emerging as a key trend in museum sustainability and communication effectiveness studies. Existing research predominantly adopts a design perspective, evaluating designs based on aesthetic and functional needs, while neglecting the influence of consumers’ cultural identity. This study investigates the influence of cultural identity on Chinese consumers’ willingness to purchase museum cultural products. To achieve this, we developed a Cultural Identity Model (CIM) based on the Technology Acceptance Model (TAM). Based on the analysis of data from 404 respondents, Chinese consumers do not perceive cultural identity (P = 0.476), ethnic identity (P = 0.482), or religious identity (P = 0.242) associated with museum cultural creative products as influential factors in their purchase decisions. However, they focus on the product attributes of cultural and creative designs (materials, colors, P = 0.042) as well as functional attributes (practicality, usability and durability, P < 0.01), all of which effectively enhance consumers’ purchase intention. Grounded in the cultural identity perspective, this study investigates determinants that actively catalyze purchase behavior toward museum-based cultural and creative products. The findings deliver novel design frameworks and theoretical foundations for the cultural and creative products development. This study provides empirical support for optimizing the design of museum cultural and creative products, and suggests focusing on the integration of functional attributes (such as practicality) and carriers of perceived cultural symbols (such as materials and colors).